Bridled tern survey report – Bajigal and Bimi (supplementary island threat assessment) (Great Barrier Reef Marine Park Authority, 2026)
This report presents the findings of a targeted field study investigating bridled tern (Onychoprion anaethetus) breeding habitat on Bajigal (Stephens Island) and Bimi (Sisters Island), located on Mandubarra Country in north Queensland. The study aimed to inform the development of the Bajigal Habitat Restoration Plan by identifying the extent and characteristics of nesting areas, and estimating nest density and population size across both islands. Field investigations documented the spatial distribution of nesting activity and key habitat attributes associated with breeding sites, providing insight into the ecological requirements of the species within this island system. Bajigal and Bimi support regionally and globally significant populations of bridled terns, with Bajigal in particular recognised as a key breeding site within Australian waters. The findings contribute to an improved understanding of habitat use and support evidence-based management to protect and enhance critical seabird breeding areas within the Great Barrier Reef World Heritage Area. This work forms a key deliverable under the Restoration of Reef Islands Project, delivered through the Reef Joint Field Management Program (Great Barrier Reef Marine Park Authority and Queensland Parks and Wildlife Service) in partnership with Mandubarra Land and Sea Inc, and Aestra as the environmental delivery partner, and funded by the Australian Government’s Reef Trust. The project aims to support the rehabilitation, enhancement, and long-term resilience of island ecosystems within the Great Barrier Reef World Heritage Area.
Aestra, 2025, Bridled tern survey report – Bajigal and Bimi (supplementary island threat assessment), prepared for the Reef Joint Field Management Program on behalf of the Great Barrier Reef Marine Park Authority, Commonwealth of Australia.
Keywords: Reef Ecosystems & Marine Species; Traditional owners; Weeds, pests and disease; Leading environmental practice; Far Northern Management Area